Paparan Mikroplastik dan Kualitas Sperma Pria: Scoping Review Perspektif Kesehatan Lingkungan Indonesia - Dwi Regita Cahyani; Triana Srisantyorini; Suherman Jaksa (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Background: The escalating contamination of environmental microplastics (MP) has raised increasing concern about its role in declining male reproductive health. MPs have been physically detected in human testicular tissue and semen, underscoring the importance of a systematic evidence synthesis. Objective: This scoping review consolidates evidence published between 2015 and 2025 regarding the effects of MP exposure on male fertility parameters, characterizes the underlying biological mechanisms involved, and identifies research gaps pertinent to Indonesia. Methods: Adhering to PRISMA-ScR guidelines and the PCC framework, systematic searches were conducted across five databases (PubMed/MEDLINE, Scopus, Web of Science, Google Scholar, and Portal Garuda). Of 150 retrieved records, 37 studies fulfilled the inclusion criteria (Cohen's κ = 0.82). Results: Polystyrene (PS) was the predominant polymer identified in testicular tissue (mean 11.60±15.52 particles/g) and semen (0.23±0.45 particles/mL). MP exposure was associated with reductions in sperm motility, vitality, and concentration alongside elevated DNA fragmentation, mediated through four pathways: oxidative stress, blood-testis barrier (BTB) disruption, endocrine interference, and spermatogenic apoptosis. Downregulation of sperm-oocyte fusion genes (DCST1, IZUMO1, SPACA6) constituted an additional reproductive risk dimension. Conclusion: Converging evidence indicates that MPs can impair male fertility through multiple toxicological mechanisms, though definitive causal evidence in humans remains lacking. As one of the world's top contributors of plastic waste to the ocean, Indonesia bears a disproportionately high exposure burden relative to its available reproductive health data. Prospective epidemiological research and the application of the precautionary principle in national plastic policy are urgently warranted.